Evaluating the Potential for Denitrification in PICP - Brown, Luke (Department of Civil Engineering, 2024)
Urbanisation has led to an increase in impermeable surfaces that often act as waterways during rainfall events and aid in the transportation of pollutants to nearby water sources, such as dams or rivers. The nitrogen compounds are major pollutants, particularly nitrate (NO3 - ) and ammonia (NH3), which facilitate eutrophication and toxic algal growth. Many stormwater control measures (SCMs) successfully manage the stormwater runoff flows, however many are ineffective at removing the pollutants present within stormwater. This has led researchers to investigate how alternative systems, such as permeable pavements (PPs), can remove stormwater pollutants. Although studies have found PPs to be effective at removing NH3 and other pollutants, PPs are largely ineffective at removing NO3 - and in most cases have caused an increase in NO3 - concentration in PP effluent through the oxidation of NH3 compounds. Some studies on nitrogen removal in PPs have recommended the inclusion of a submerged zone to improve denitrification. Since permeable interlocking concrete pavements (PICPs) are the most widely used PP structure internationally, this study investigated the potential for denitrification in PICP through the incorporation of a submerged zone in its structure. It considered the three main factors controlling denitrification: (1) detention time, (2) inclusion of a carbon source (newspaper) and (3) submerged zone depth. The impact that these factors had on NH3 and phosphate (PO4 3- ) removal in a submerged zone were also investigated. This study used ten columns, each fully packed with 50-63 mm washed aggregate and included a 1.5 m deep submerged zone. The submerged zone of each column was fitted with taps (sample ports) spaced at 300 mm intervals from 0 to 1500 mm. Columns were paired according to detention time (1, 2, 5, 10 and ‘varied' days) with one set including newspaper as the carbon source, while the other set not. All columns were loaded with synthetic stormwater over a four-month period. Samples were taken from different submerged depths (0, 300, 600, 900, 1200 and 1500 mm) of each column and analysed for concentrations of NH3, NO3 - and PO4 3- . This study found that 10 (or more) days detention and providing a carbon source have the most significant impact on denitrification – providing an overall mean NO3 - and nitrogen removal of 41 and 59% respectively. Moreover, a submerged depth of 300 mm was sufficient to achieve a minimum NO3 - removal of 41% in columns which included a carbon source and had 10 days detention. An increase in detention time allowed for a decrease in both NH3 and PO4 3- concentration. The longest detention time of 10 days provided an overall mean NH3 and PO4 3- removal of 86% and 30%, respectively. However, the inclusion of a carbon source had no significant impact on NH3 and PO4 3- removal. In most cases an increase in submerged depth resulted in an increase in NH3 concentration from 600 to 1500 mm, and a decrease in PO4 3- concentration from 0 to 900 mm. This study concluded that PICP has the potential to significantly reduce NH3, NO3 - and PO4 3- compounds present in stormwater through the incorporation of a submerged zone, and thus ultimately improve the quality of water entering our water sources.